Anatomy & physiology for dummies - Odya, E, Norris, M.; Norris, Maggie; Odya, Erin (New jersey John wiley, 2017)
Combines anatomical terminology and function so readers not only learn names and terms but also gain an understanding of how the human body works. Readers of this updated edition will come to understand the meanings of terms in anatomy and physiology, will get to know the body's anatomical structures, and will gain insights into how the structures and systems function in sickness and health.--
Includes index.
Previous edition: 2016.
Keywords: Human anatomy; Human physiology; SCIENCE / Life Sciences / Human Anatomy & Physiology